The combination of several RCBDs - Usman, Mustofa; Njuho, Peter; Elfaki, Faiz Ahmed Mohamed; Daoud, Jamal Ibrahim (INSI Publications, 2011)
The application of Experimental Design nowadays is very extensive in many research areas, especially in Engineering, Agriculture, Education and Life sciences. In many experimental designs sometimes the researchers want to compare parameters from some design of experiments. This paper will discuss the approach to combine several RCBDs (Randomized Complete Block Designs) for the fixed effect model. The combined model is non full column rank and has constraint on its parameters. The approach used in this paper is MRM (Model Reduction Method) to transform the constrained model into unconstrained model. Then the analysis of interest will be based on the unconstrained model.